The Longevity-Associated SH2B3 (LNK) Genetic Variant: Selected Aging Phenotypes in 379,758 Subjects - Kuo, Chia-Ling (J Gerontol A Biol Sci Med Sci, 2019)
Human SH2B3 is involved in growth factor and inflammation signaling. A SH2B3 missense variant (rs3184504) is associated with cardiovascular diseases plus breast, colorectal, and lung cancers, with highly correlated variants across the ATXN2/SH2B3/BRAP locus linked to parental age at death, suggesting a geroscience common mechanism of aging and disease. To better understand the SH2B3-related aging pathway and its potential as an intervention target, we undertook a phenotype-wide association study (PheWAS) of 52 aging traits. Data were obtained from 379,758 European-descent UK Biobank participants, aged 40–70 at baseline: 27% of participants were CC homozygotes and 23% TT at rs3184504. Parental extreme longevity (mothers aged ≥98 years, fathers aged ≥96 years) was more common in CC versus TT (odds ratio [OR] = 1.18, 95% confidence interval [CI]: 1.07 to 1.29) with an additive per allele effect. The C allele associated with better cognitive function and white blood cell counts were more likely to be normal. The C allele reduced risks of coronary heart disease (OR = 0.95, 95% CI: 0.93 to 0.96) but was also associated with a modestly higher cancer rate (OR = 1.03, 95% CI: 1.02 to 1.04), suggesting a trade-off across aging outcomes and limiting its potential as an anti-aging target.